Synthesis, X-Ray Diffraction, Spectroscopic (FT-IR, UV-Vis, 1H-NMR, 13C-NMR and TGA), DFT and Molecular Docking Studies of (E)-3 Phenyl) Imino) Methyl) Benzene-1,2 - Uzun, Serap; Demircioglu, Zeynep; Tasdogan, Mahmut; Agar, Erbil (Taylor & Francis Ltd, 2022)
The title compound has been synthesized and characterized by FT-IR, UV-Vis, TGA, H-1-NMR and C-13-NMR spectroscopic techniques. Solid state of title structure has been determined by XRD. The molecular properties of title compound have performed by Density functional theory (DFT) using B3LYP/6-31G(d,p) method. Also, the interactions between the title molecule with DNA bases have been calculated by using the electrophilicity-based charge transfer (ECT) method for investigating the charge transfer. Finally, molecular docking study has also performed to investigate the binding pattern of the title compound with PDB ID: 2QDJ inhibitor targets and showed good insights on the possible interactions.
Keywords: Density Functional Theory (DFT); DNA; ECT Method; Hirshfeld Surface Analysis; Molecular Docking; X-Ray Diffraction Method